Analisis Sistem Pengendalian Penerimaan dan Pengeluaran Kas sebagai Pilar Akuntabilitas Keuangan pada Perusahaan X - Devyanti Samada; Igustina Igustina; Nurhalizah Nurhalizah; Nurul Musliha Asmalyani; Ahmad Teguh Fachrezi; Alia Rezki Amalia (AKUNTANSI 45, 2025)
This study aims to determine and analyze the suitability of the implementation of the internal control system over cash receipts and expenditures in Company X with the internal control framework according to COSO theory. The research method used is qualitative descriptive, which allows researchers to gain an in-depth understanding of the process, staff views, and background behind each cash control procedure implemented by the company. The results of the study show that the internal control system at Company X in general has run well and is in line with the COSO components, including through systematic recording, tiered authorization, adequate separation of duties, and the implementation of internal audits. This implementation contributes to improved cash security, reliability of record-keeping, and transparency of financial statements. However, weaknesses were found in the aspect of activity control, especially related to delays in receivables collection and no follow-up on delinquent customers. This condition has the potential to reduce the effectiveness of overall cash control. Therefore, although the foundation of the company’s internal control has been strong, it is necessary to improve the discipline of collection and receivables monitoring in order for the effectiveness of the internal control system to be optimized.